Microwave Photonic Fiber Ring Resonator - Chen Zhu; Yiyang Zhuang (Sensors, 2022)
In this article, a new concept of microwave photonic (MWP) fiber ring resonator is introduced. In particular, the complex transmission spectra of the resonator in the microwave domain, including magnitude and phase spectra, are measured and characterized. Multiple resonance peaks are obtained in the magnitude spectrum; rapid variations in phase near resonance (i.e., enhanced group delay) are observed in the phase spectrum. We also experimentally demonstrate that the MWP fiber ring resonator can be potentially employed as a novel optical fiber sensor for macro-bending and fiber length change sensing (strain sensing). The experimental results are in good agreement with theoretical predictions.